Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) - Yudia Suryatama; Arwin Arwin (Universitas Negeri Padang, 2020)
This research is motivated by the low learning implementation plan, teachers in implementing integrated thematic learning and student learning outcomes. This type of research is Classroom Action Research using qualitative and quantitative approaches. The research procedure was preceded by planning, implementing, observing, and reflecting. Data collection techniques in the form of observation and tests. This research was conducted in Semester I of the 2020/2021 academic year. The research subjects were the teacher as the observer, the researcher as the practitioner, and 12 grade V students consisting of 6 male students and 6 female students.The results of the first cycle research on RPP an average of 75.79% (enough), increased in the second cycle to 92.85% (very good). Implementation of the first cycle in teacher activity on average 75% (enough), increased in the second cycle to 96.42% (very good). The implementation of the first cycle in student activities an average of 71.45% (enough), increased in the second cycle to 96.42% (very good). Student learning outcomes in the first cycle an average of 63.49 (less), increased in the second cycle to 80.40 (good). Thus, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in integrated thematic learning in elementary schools.